Evaluating the Role of BRICS in Shaping Global Economic Governance: A Comparative Analysis of Policy Approaches and Outcomes - Haryono, Haryono; Utari, Woro; Rahmawati, Diah Ayu; Endarto, Budi; Sanusi, Ruchan (Eastasouth Institute, 2024)
This study evaluates the role of BRICS (Brazil, Russia, India, China, and South Africa) in shaping global economic governance through a normative analysis of policy approaches and outcomes. By examining the collective strategies and individual priorities of BRICS nations, the research highlights their contributions to global economic equity, inclusivity, and sustainability. Key initiatives, such as the New Development Bank (NDB) and the Contingent Reserve Arrangement (CRA), are analyzed to assess their practical impact and alignment with normative principles. While BRICS has made significant strides in promoting reforms and fostering multilateral cooperation, internal tensions and geopolitical challenges have limited its ability to present a cohesive front. This study concludes that BRICS has substantial potential to redefine global governance, provided it strengthens internal unity and enhances its normative vision for a more inclusive international system.